2012
DOI: 10.1073/pnas.1202068109
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor of activated T cells (NFATc4) is required for BDNF-dependent survival of adult-born neurons and spatial memory formation in the hippocampus

Abstract: New neurons generated in the adult dentate gyrus are constantly integrated into the hippocampal circuitry and activated during encoding and recall of new memories. Despite identification of extracellular signals that regulate survival and integration of adult-born neurons such as neurotrophins and neurotransmitters, the nature of the intracellular modulators required to transduce those signals remains elusive. Here, we provide evidence of the expression and transcriptional activity of nuclear factor of activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 62 publications
3
43
0
Order By: Relevance
“…These findings are in good agreement with our previous molecular and functional data indicating that NFATc3 is the predominant NFAT isoform in DRG neurons (7,33). However, given that the expression and roles of specific NFAT isoforms vary among different types of neurons (4,8,12,13,28), it is likely that other NFAT isoforms are also regulated by neurotrophins. For example, NFATc4 is targeted by BDNF in hippocampal neurons (12,13,28).…”
Section: Casupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in good agreement with our previous molecular and functional data indicating that NFATc3 is the predominant NFAT isoform in DRG neurons (7,33). However, given that the expression and roles of specific NFAT isoforms vary among different types of neurons (4,8,12,13,28), it is likely that other NFAT isoforms are also regulated by neurotrophins. For example, NFATc4 is targeted by BDNF in hippocampal neurons (12,13,28).…”
Section: Casupporting
confidence: 92%
“…However, given that the expression and roles of specific NFAT isoforms vary among different types of neurons (4,8,12,13,28), it is likely that other NFAT isoforms are also regulated by neurotrophins. For example, NFATc4 is targeted by BDNF in hippocampal neurons (12,13,28). By monitoring the nuclear translocation of EGFP-NFATc3 in DRG neurons in real time, we found that NGF and GSK3␤ inhibited nuclear export of NFATc3 but had no detectable effect on the rate of nuclear import of NFATc3 (Figs.…”
Section: Camentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the nuclear factor of activated T cell (NFAT) transcription factors have an important role in the development of the nervous system 7,8 and in the control of the survival/death fate of neurons. [9][10][11][12][13][14] The NFAT family comprises four calcium/calcineurindependent transcription factors that are encoded by four closely related genes. [15][16][17] NFAT proteins are expressed in most mammalian tissues, with the different members of the family being present in distinct but overlapping sets of cell types.…”
mentioning
confidence: 99%
“…Both NFATc3 and NFATc4 have been shown to have either proapoptotic or antiapoptotic effects, depending on the physiologic and cellular context. [9][10][11][12][13][14][20][21][22] However, the mechanisms that regulate their activity in response to apoptotic stimuli and the target genes that mediate their differential effects on neuronal apoptosis are mostly unknown.…”
mentioning
confidence: 99%